Autonomy in labour and delivery in a Latin American urban centre: a qualitative phenomenological analysis - Maribel Mella-Guzmán; Lorena Binfa; Fiona Weeks (Sexual and Reproductive Health Matters, 2023)
The medicalisation of childbirth has diminished the role of labouring people. We conducted an exploratory phenomenological qualitative study, using purposive sampling, and then conducted 17 semi-structured interviews between December 2016 and October 2017 with people who had recently given birth in a public hospital in the Northern Metropolitan area of Santiago, Chile. The sufficiency of the study group was determined according to saturation criteria. Triangulated content analysis was applied to explore the clinical relationship and processes of autonomy and decision-making. The predominant clinical relationship observed was paternalism. The participation of labouring people in decision-making is scarce, with no evidence of ethically valid processes of informed consent.